MENINGKATKAN KEMAMPUAN MEMBACA NYARING MENGGUNAKAN MEDIA CERITA BERGAMBAR PADA MATA PELAJARAN BAHASA INDONESIA UNTUK SISWA KELAS II SD NEGERI MINASA UPA MAKASSAR - Riska Hasan; M. Agus; Haslinda Haslinda (Simpati, 2023)
This research is a class action research (classroom action research) which consists of two cycles, aimed at improving the ability to read aloud in the Indonesian language subject for second graders of SD Negeri Minasa Upa Makassar through the use of picture story media. The subjects in this study were class II students of SD Negeri Minasa Upa Makassar with a total of 26 students consisting of 14 male students and 12 female students. The research was carried out using two cycles, each cycle consisting of 3 meetings in accordance with the changes to be achieved. The first and second meetings were carried out with the learning process, and the third meeting was for the assessment of reading aloud skills. Each cycle consists of several activities in the assessment according to the nature of the assessment. The two cycles were carried out for 3 months plus summarizing all the results of existing research.The results showed that from cycle I, the learning completeness only reached 27% with an average of 62.5 then increased to 100% in cycle II with an average of 82.9 in connection with the conclusions above, it can be concluded that in applying learning media that just like the use of picture story media in Indonesian language subjects, especially in the aspect of reading aloud.